Using Economic Model To Improve The Performance Of BHR Dynamic Replication Algorithm. - Kanesin, Yogita; Sodhy, Gian Chand (2007)

(untitled)
In grid computing environment, data is often replicated on many different sites to reduce access time. Static replication fixes the number of replicas whereas dynamic replication adapts to the demands of the grid by reducing or increasing the number of replicas or even moving the location of a replica to another site.